Observations on an unusual behaviour in the Carpenter Bee Xylocopa aestuans (Latreille, 1802) (Hymenoptera: Apidae) of the Western Ghats, India - S.A. Punekar; N.K.P. Kumaran; H.R. Bhat (Journal of Threatened Taxa, 2010)
The Carpenter Bee Xylocopa aestuans is a known pollen and nectar feeder. However, at Anshi National Park of Karnataka (India), the bee happens to be switching over to facultative carnivorous habit as they are found to feed on Red Tree Ants Oecophylla smaragdina. Such a kind of carnivorous feeding habit must have existed which is yet to be reported.